PERGESERAN NILAI TRADISI BEDAPUR PASCA PERSALINAN PADA PEREMPUAN GAYO LUES - Meliza, Richa; Harinawati, Harinawati; Ameliany, Nanda; Faisal, Naidi (FISIP Universitas Malikussaleh, 2024)
Culture or tradition can survive if there are people who preserve and practice it. Traditions will live and develop according to the times if people still maintain these habits. However, the tradition is weakened and eroded by the masses due to the increasing knowledge and understanding of the community about the tradition, especially the